ANALYSIS OF FACTORS AFFECTING FINANCING TO DEPOSIT RATIO (FDR) AT ISLAMIC COMMERCIAL BANKS IN INDONESIA - Yeni Fitriani Somantri; Wawan Sukmana (Berkala Akuntansi dan Keuangan Indonesia, 2019)
The purpose of this study is to determine and analyze what factors are able to influence the level of liquidity distribution of funds/financing at Islamic Commercial Banks in Indonesia. The data analysis technique in this study was carried out with multiple regression using SPSS software. The method used in this study is explanatory research, which emphasizes the relationship between research variables (dependent variables and independent variables) and hypothesis testing (hypothesis testing) to test the proposed hypothesis regarding the effect of third party funds (TPF), return on assets ( ROA), non-performing financing (NPF), and the inflation rate as factors that influence the level of liquidity in the distribution of funds/financing of Islamic banks in Indonesia. The results showed that third party funds (DPK), return on assets (ROA), non-performing financing (NPF), and the inflation rate had a significant effect, either partially or simultaneously.